DETERMINANTS OF ENVIRONMENTAL RISK MANAGEMENT AT WORK PLACE DURING AND AFTER PANDEMIC SITUATIONS (Contemporary Journal of Social Science Review, 2024)
The research aims to explore and order the factors of environmental risk management at the workplace during and after the period of a pandemic. The design of the research covers the examination of contemporary literature, data collection, analysis, and implications. Through literature examination, a list of determinants is generated which subsequently is approved by a panel of experts. The panel of experts consists of sixteen members from among the heterogeneous groups of stakeholders (i.e. environmental experts/representatives), drawn based on the purposive sampling technique. The population under study is the stakeholders of the environment. The methodology used is ISM and MICMAC. The results of the studies are aligned with the literature upcoming. As per the findings of ISM, the factor ‘level of company operations’ falls on Level I and is considered the least critical factor. The factor ‘environmental analysis of business activities’ falls at Level III and is considered the most important factor. As per MICMAC, the factor ‘level of company operations’ is categorized as a dependent variable. All the rest variables are linkage variables. Being the first study that explores factors of environmental risk management in the workplace, it adds to the literature valuable insights. The research has insightful implications for ecological regulatory authorities, agencies, the international community, researchers, policymakers, and the persons responsible in the industry for environmental harmony since it provides valuable information/insights for deepening the understanding of the phenomenon.